Advanced triboelectric nanogenerators based on low-dimension carbon materials: A review. (July 2022) - Cheng, Kuan; Wallaert, Samuel; Ardebili, Haleh; Karim, Alamgir
Abstract: Conventional methods to harvest and supply energy are challenged by the ever-increasing demand for versatile forms of electrical energy caused by the rapid expansion of new devices, often related to the Internet of Things (IoT) and 5G networks. As an emergent solution for some applications, flexible triboelectric nanogenerators (TENGs) have the potential to scavenge mechanical energy from a range of motion-related energy capture, such as arbitrary wind drifts, making it a portable solution to energy generation on-demand in the future. Much research has focused on enhancing the output power of TENGs to its maximum limit. Choosing the desirable material pair with high work function difference, increasing contact surface area between materials, and designing an efficient device structure, are deemed to be the three most dominant tasks. Incorporating low-dimension (e.g., 1D, 2D) carbon materials, including graphene and carbon nanotubes, can bring many synergistic properties to TENGs, such as output enhancement and multifunctionality, which has garnered much recent interest. This article systematically reviews the latest efforts in newly designed TENG devices by low-dimension carbon materials, from fundamentals to applications. The challenges and unique perspectives encountered by these materials are also discussed in depth. Graphical abstract: Image 1 Highlights: Nearly complete lists of latest triboelectric nanogenerator designs based on graphene and graphene oxide were presented. Latest works on low-dimension carbon nanomaterials based TENG were reviewed by their structure, performance, and application. The review is structured by classifying the TENG material selections into different dimensions. Challenges and further development towards carbon-based triboelectric nanogenerators were provided.